PENGARUH KOMPENSASI DAN MOTIVASI TERHADAP KINERJA PEGAWAI PADA DEPARTEMEN SUMBER DAYA MANUSIA PT. COLUMBINDO PERDANA - Nasrun Yusuf (MIX: JURNAL ILMIAH MANAJEMEN, 2014)
Abstract: This thesis was made in order to determine how much ofthe correlation of compensation and motivationon the performance of Pegawai Departemen SDM, PT. Columbindo Perdana. The method used in this research is descriptive and qualitative with path analysis. Data collection method used is through the study of literature, observation and interviews. The study was conducted at the Human Resource Departement on PT. Columbindo Perdana, the number of respondents 64 people. From these results it is known that the compensation and motivation has apositive and significant correlation to the performance of the company, in this case PT. Columbindo Perdana. Compensation has a higher correlation to the performance of the company compared to the motivation.Keywords: compensation, motivation, performance